Inhibition of breast cancer cell growth by the combination of clofarabine and sulforaphane involves epigenetically mediated CDKN2A upregulation. (4th May 2018) - Lubecka, Katarzyna; Kaufman-Szymczyk, Agnieszka; Fabianowska-Majewska, Krystyna
ABSTRACT: Many antineoplastic nucleoside analogue-based combinatorial strategies focused on remodelling aberrant DNA methylation patterns have been developed. The number of studies demonstrate high efficacy of bioactive phytochemicals in support of conventional chemotherapy. Our recent discoveries of the epigenetic effects of clofarabine (2′-deoxyadenosine analogue, antileukaemic drug) and clofarabine-based combinations with dietary bioactive compounds in breast cancer cells led us to look for more DNA methylation targets of these cancer-preventive agents. In the present study, using methylation-sensitive restriction analysis (MSRA) and qPCR, we showed that clofarabine in combination with sulforaphane, a phytochemical from cruciferous vegetables, significantly reactivates DNA methylation-silenced CDKN2A tumour suppressor and inhibits cancer cell growth at a non-invasive breast cancer stage.